Nanowires Synthesis, Properties and Applications - Rackauskas, Simas (IntechOpen, 2019)
Nanowires are attracting wide scientific interest due to the unique properties associated with their one-dimensional geometry. Developments in the understanding of the fundamental principles of the nanowire growth mechanisms and mastering functionalization provide tools to control crystal structure, morphology, and the interactions at the material interface, and create characteristics that are superior to those of planar geometries. This book provides a comprehensive overview of the most important developments in the field of nanowires, starting from their synthesis, discussing properties, and finalizing with nanowire applications. The book consists of two parts: the first is devoted to the synthesis of nanowires and characterization, and the second investigates the properties of nanowires and their applications in future devices.